2010
DOI: 10.1111/j.1754-9485.2010.02200.x
|View full text |Cite
|
Sign up to set email alerts
|

Microcystic adnexal carcinoma of the skin: The role of adjuvant radiotherapy

Abstract: While Mohs micrographic surgery may be considered the gold standard, wide local excision and adjuvant radiotherapy offers comparable control rates. Doses of 50 Gy or greater should be prescribed with generous margins (3-5 cm) owing to its tendency for peri-neural and deep invasion. There was no evidence that radiotherapy can cause aggressive transformation of the tumour. The role for definitive radiotherapy remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 32 publications
0
40
1
2
Order By: Relevance
“…Stein et al . suggested that definitive radiotherapy for adnexal carcinomas has resulted in a clinically aggressive transformation which we cannot comment on in our study as none of the patients received radical radiotherapy; however, one patient who did not have radiotherapy post-tumor resection developed locoregional recurrence [11, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…Stein et al . suggested that definitive radiotherapy for adnexal carcinomas has resulted in a clinically aggressive transformation which we cannot comment on in our study as none of the patients received radical radiotherapy; however, one patient who did not have radiotherapy post-tumor resection developed locoregional recurrence [11, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…Other single institution, small case series have demonstrated similar local control rates with adjuvant RT ranging from 93-100%. 14, 24 In those two small series, varied radiation techniques were used and indications for radiation were primarily PNI and positive margin. No patients in these series had lymph node positive disease, whereas almost 50% of our patients did.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to excision, radiotherapy was given to our patient. Although the use of adjuvant radiotherapy has been debatable, a recent study supported its efficacy [10].…”
Section: Discussionmentioning
confidence: 98%